Optic Nerve Drusen Is Highly Prevalent Among Children With Pseudotumor Cerebri Syndrome - Genizi, Jacob; Meiselles, Doron; Arnowitz, Elisheva; Segal, Idan; Cohen, Rony; Goldenberg-Cohen, Nitza (Frontiers in Neurology, 2021)
IIntroduction: The clinical presentation of pseudotumor cerebri syndrome (PTCS) usually includes headache, nausea and vomiting, with normal physical examination apart from papilledema and diplopia. However, pseudopapilledema , which can be caused by optic nerve drusen, may lead to misdiagnosis. The prevalence of optic nerve drusen in the general population is 0.5–2%. The purpose of our study was evaluate the prevalence and risk factors of optic nerve drusen among patients with PTCS. Materials and Methods: Medical records of children evaluated in the pediatric department at Bnai Zion Medical Center due to PTCS between 2008 and 2020 were assessed. Inclusion criteria were children age under 18 years with a PTCS diagnosis and ophthalmic B-mode ultrasonography (US). Exclusion criteria were secondary intracranial hypertension. Results: Thirty four children were included, mean age 10.1 years, 50% boys. A majority of the patients, 24 (72.4%), complained of headaches, while 15 (45.5%) complained of transient visual obscuration and 9 (26.5%) of vomiting. Visual acuity on presentation was normal (20/20–20/30) in 23 of the children (67%), moderately diminished (20/40–20/80) in 9 (26%), and showing profound loss (20/200) in 2 (7%). Five patients (14.7%) were diagnosed with optic nerve drusen via B-mode ophthalmic ultrasonography (US); however, they still fulfilled the diagnostic criteria for PTCS, and disc swelling improved after treatment. There were no statistically significant differences between the group with optic nerve drusen and the rest of the patients. Conclusions: Optic nerve drusen are common among pediatric patients with PTCS. Diagnosis of optic nerve drusen should not rule out the presence of increased intracranial pressure.